MEMBANGUN KEADILAN DAN KESETARAAN PEMBELAJARAN DALAM PERSPEKTIF FILSAFAT PENDIDIKAN INKLUSI - Adilah Wina Fitria (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2024)
This article aims to explore the concept of inclusive education and emphasize the concepts of justice and equality in PAUD learning. The approach taken in this article is theoretical research, which links three philosophical foundations, namely ontology, epistemology and axiology to understand how to implement inclusive education fairly and equally. Based on this research, the Ontology of Inclusive Education explains that every child, regardless of ability or background, has the same right to learn in an environment that supports diversity. Epistemology emphasizes the importance of an adaptive approach to learning, where each child acquires knowledge in a way that suits his or her needs. Axiology emphasizes the values of social justice, cooperation and respect for differences, which must be applied in the learning process to build a more inclusive society. This article also discusses the challenges of implementing inclusive education and provides recommendations for increasing educational equality and the quality of education for all children in PAUD. Through this philosophy-based approach, inclusive education in PAUD can provide equal and sustainable opportunities for every child to develop according to their potential.